COASTAL THEMATIC DATA INVENTORY FOR COASTAL RESOURCE MONITORING, MANAGEMENT AND PLANNING - Kardono, Priyadi; Rusmanto, Adi (MAJALAH ILMIAH GLOBE, 1999)
Indonesia is the most populated and the largest archipelagic country in the world. It consists of more than 17.500 islands and the length of coast line is approximately 81,000 kilometers. The coastal area accommodates for approximately 22% of the total population and very complex human activities such as shipping, industries, aquaculture, tourist resort, real estate, power plant, commerce building, etc. Therefore, if coastal zone planning was not better prepared, this will lead to uncontrolled land use.The complexity of coastal management requires current and accurate data and information, which consist of statistics and maps. The availability of data and information which meet the specification is another problem in coastal management. However, Geographic Information System (GIS) can analyze accurately and quickly spatial data and build natural resource database. Because many institutions were involved in the preparation of natural resource maps, there would be also a problem in preparing the thematic database. Therefore, by integrated preparation, which is doing database preparation in Bappeda of 10 Provinces, the problem can be solved.ABSTRAKlndonesia sebagai negara kepulauan yang terpadat dan terluas di dunia memiliki lebih dari 17.500 pulau dengan panjang garis pantai sekitar 81.000 km. Wlayah pesisirnya dihuni oleh sekitar 22% penduduk Indonesia dengan berbagai kegiatannya, sehingga apabila wilayah pesisir tidak dikelola dengan baik akan menimbulkan penggunaan lahan yang tidak terkontrol. Rumitnya pengelolaan wilayah pesisir membutuhkan data dan informasi yang baru dan akurat dalam bentuk data statistik ataupun peta. Ketersediaan data yang sesuai dengan kebutuhan juga merupakan masalah dalam pengelolaan wilayah pesisir. Namun demikian Sistim lnformasi Geografis dapat dengan tepat dan cepat menganalisa data spasial dan membangun basisdata sumberdaya alam. Karena penyediaan peta sumberdaya alam melibatkan berbagai institusi, terdapat kendala pula dalam penyusunan basisdata tematik. Untuk itu penyusunan basisdata tematik ini dilaksanakan di 10 Bappeda.